2018
DOI: 10.1371/journal.pone.0208749
|View full text |Cite
|
Sign up to set email alerts
|

Exercise stress CMR reveals reduced aortic distensibility and impaired right-ventricular adaptation to exercise in patients with repaired tetralogy of Fallot

Abstract: BackgroundThe aim of our study was to evaluate the feasibility of exercise cardiac magnetic resonance (CMR) in patients with repaired tetralogy of Fallot (RTOF) and to assess right and left ventricular adaptation and aortic wall response to exercise in comparison with volunteers.Methods11 RTOF and 11 volunteers underwent prospective CMR at rest and during exercise. A supine bicycle ergometer was employed to reach twice the resting heart rate during continuous exercise, blood pressure and heart rate were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…The seminal Ex-CMR study in repaired ToF patients by Roest et al demonstrated an abnormal RV response to exercise compared with controls, but a decrease in pulmonary regurgitation [117]. A more recent study demonstrated reduced biventricular contractile reserve and aortic distensibility in repaired ToF patients compared to healthy subjects during Ex-CMR, which may be an early sign of increased aortic rigidity [121].…”
Section: Khiabani Et Al Demonstrated the Association Of Exercisementioning
confidence: 99%
See 2 more Smart Citations
“…The seminal Ex-CMR study in repaired ToF patients by Roest et al demonstrated an abnormal RV response to exercise compared with controls, but a decrease in pulmonary regurgitation [117]. A more recent study demonstrated reduced biventricular contractile reserve and aortic distensibility in repaired ToF patients compared to healthy subjects during Ex-CMR, which may be an early sign of increased aortic rigidity [121].…”
Section: Khiabani Et Al Demonstrated the Association Of Exercisementioning
confidence: 99%
“…Ex-CMR has been demonstrated as feasible in repaired ToF in both adults [121] and children [85]. The seminal Ex-CMR study in repaired ToF patients by Roest et al demonstrated an abnormal RV response to exercise compared with controls, but a decrease in pulmonary regurgitation [117].…”
Section: Khiabani Et Al Demonstrated the Association Of Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, CMR by late gadolinium enhancement (LGE) is the noninvasive reference standard for replacement brosis detection, with signi cant diagnostic and prognostic implications. Pharmacological stress-CMR can be performed using either inotropic (dobutamine) or vasodilator (adenosine or dipyridamole) stimuli [17] and recent studies have demonstrated the feasibility of exercise stress test, acquiring images immediately following maximal treadmill exercise or with in-scanner cycle ergometers [18,19]. Nevertheless, currently vasodilator stress agents remain the mainstay of stress-CMR due to safety issues [20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CMR by late gadolinium enhancement (LGE) is the noninvasive reference standard for replacement brosis detection, with signi cant diagnostic and prognostic implications. Pharmacological stress-CMR can be performed using either inotropic (dobutamine) or vasodilator (adenosine or dipyridamole) stimuli [17] and recent studies have demonstrated the feasibility of exercise stress test, acquiring images immediately following maximal treadmill exercise or with in-scanner cycle ergometers [18,19]. Nevertheless, currently vasodilator stress agents remain the mainstay of stress-CMR due to safety issues [20].…”
Section: Introductionmentioning
confidence: 99%